Horticultural producers in Costa Rica: diagnosis of resources and capabilities - Picado, Rytha (2025)
Abstract Addressing the challenges and opportunities of the horticultural sector requires, as a first step, knowing the status of the involved actors. This article aims to characterize horticultural producers linked to a Cantonal Agricultural Center of Costa Rica in terms of their resources and capacities to address a significant gap in the existing literature regarding the characteristics of the horticultural supply chain in the country. The research used a qualitative approach based on in-depth interviews conducted during March 2024 and focused on producers from one of the most representative and key regions for horticultural production. The findings show that most producers are men with primary education and experience of approximately three decades in agriculture, who market mainly at farmers' fairs. There is good road access to the productive areas. Most have the essential equipment, such as back pumps and vehicles, but the presence of more specialized equipment and facilities, such as irrigation systems, greenhouses, or biofactories, is limited. The study also reveals that they have received support from various organizations and lack formal financial support. These results underscore the need to improve resource and capacity management to strengthen the supply chain and sustainability of horticultural production, which can consequently promote its competitiveness and permanence in the activity